(3TQM GHf edc Ydi eLeY GdHMQjfs - (3YHO GddWja Hf YHO GdYRjR Hf Cejf GdOjf Hf aQTJG GdcQeGfj, GdeYQha HGHf edc,J (B801 (3g` s; (3Ydj Hf eMeO Hf QSJe Hf gQOhR, CHh GdMSf, HgGA GdOjf GHf GdSGYGJj,J (B604 (3g` s
(3ChdgG (B:s
(3EfgG de JSJMbgG YfO GdWdGb adGjSJMbgG HGdEMJHGS HYOg s
(3BNQgG (B:s
(3ehSi Ydjg GdSdGe hSGQ HCgdg Ci HRhLJg hdg ehGdi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B330 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B62s
(3cTa GdXfhf (B- (3GdLRA (B2 - (3U (B1599 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1601s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3Gdabg GdMfajs